Effect of Variations of Temperatures on the Compatibility of Poly(Methyl Methacrylate)/Polyvinyl Chloride in THF Ternary System - Melad, Omar; Baraka, Rajai; K.J. Salem, Jamil (Asian Journal of Chemistry, 2010)
The intermolecular interaction between poly (methyl methacrylate) (PMMA) and polyvinyl chloride (PVC) in THF has been studied at different temperatures using dilute-solution viscometry method. The intrinsic viscosity and viscometric interaction parameter were experimentally measured for the binary (solvent/polymer) and ternary (solvent (1)/polymer (2)/polymer (3) systems. These results have served for the estimation of the compatibility of the polymer mixture at different temperatures by means of the sign of Δbm and Δ [ η ]m . The results show that the polymer mixture is compatible in THF as the temperature increases, while the incompatibility observed at 34°C may be due to the enhancement in the interactions between THF and the polymers at this temperature.